CORPORATE SOCIAL RESPONSIBILITY AND SOCIAL INNOVATION: DRIVING POSITIVE CHANGE THROUGH BUSINESS PRACTICES - Bhilare, Meghana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
By bringing business objectives into line with societal demands, social innovation and corporate social responsibility (CSR) have emerged as key forces behind sustainable development. This research paper discuss how innovative social strategies and corporate social obligation efforts can also enhance enterprise strategies. The research investigates the relationship between social innovation and corporate social responsibility in improving a company's financial performance, stakeholder engagement, and reputation using a sample of 225 respondents. 28 questions were used in the quantitative data analysis, which revealed important variables affecting the efficacy of CSR and how it integrates with social innovation. According to the results, businesses that actively are seeking for CSR and social innovation are much more likely to have long-term success and favorable social effects. The present research provides the expanding corpus of facts on sustainable business practices and provides useful records for academic researchers, business executives, and legislators.